Exercise capacity in apparently healthy survivors of cancer - De Caro, E (BMJ Group, 2006)
AIMS: To evaluate cardiopulmonary exercise tolerance in a large cohort of apparently healthy paediatric cancer survivors in order to determine their participation in sporting activities. METHODS: A total of 84 young (<21 years) asymptomatic childhood cancer survivors, who had been exposed to anthracyclines (mean dose 212 mg/m(2)) and/or chest irradiation (median dose 2000 cGy), with normal left ventricular systolic function at rest (fractional shortening >29%), and 79 healthy controls were studied. Exercise testing was performed on a treadmill ergometer. Gas exchange analysis and derived variables were measured on a breath‐by‐breath basis. Pulmonary functional evaluation was performed before exercise. Echocardiographic evaluation at rest was performed within one month before the exercise test. RESULTS: There were no differences in exercise responses between patients and controls. In boys <13 years, mean VO(2) max was slightly but significantly lower than in controls. This finding was thought to be a result of decreased physical fitness as all the other exercise parameters were similar to those in the controls. CONCLUSIONS: Results show that apparently healthy survivors of paediatric cancer can take part in dynamic sporting activities if they exhibit a normal response to cardiopulmonary exercise testing, while those that exhibit a reduced VO(2) max should be re‐evaluated after an aerobic training programme, and should undergo tailored dynamic physical activity if the VO(2) max does not normalise.